2019
DOI: 10.1111/acer.14206
|View full text |Cite
|
Sign up to set email alerts
|

High Opportunity Cost Demand as an Indicator of Weekday Drinking and Distinctly Severe Alcohol Problems: A Behavioral Economic Analysis

Abstract: Introduction: Behavioral economic theory views addiction as a reinforcer pathology characterized by excessive demand for drugs relative to alternatives. Complementary to this theory, Lamb and Ginsburg (Pharmacology Biochemistry and Behavior, 164, 2018, 62) describe addiction as a behavioral allocation disorder and predict that decisions to drink under increasingly stringent constraints are a central indicator of addiction. This study used a modified demand-curve paradigm to examine alcohol demand in the conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 71 publications
(100 reference statements)
1
14
0
Order By: Relevance
“…For example, in an evaluation of change processes associated with a brief alcohol intervention (Murphy et al, 2019), emerging adults who reduced their drinking showed increased reinforcement from substance-free activities at follow-up, and changes in proportionate reinforcement related to substance-free activities mediated the relation between the intervention and reductions in alcohol use. Further, having substance-free next-day responsibilities (e.g., employment, classes, volunteer work) have been linked to lower alcohol demand, as measured by a behavioral economic task, the alcohol purchase task (Murphy & MacKillop, 2006), that quantifies hypothetical alcohol consumption and alcohol-related expenditures as a function of drink prices (Joyner et al, 2019). A review of clinical research on associations between social support and smoking (Fisher, 1996) supported conceptualizing both activities as commodities that could substitute for one another; specifically, social support is effective in reducing smoking, while it is available but this salutary substitution relationship diminishes when access is constrained.…”
Section: Present Status Of Research On Addictive Behavior As Behavior...mentioning
confidence: 99%
“…For example, in an evaluation of change processes associated with a brief alcohol intervention (Murphy et al, 2019), emerging adults who reduced their drinking showed increased reinforcement from substance-free activities at follow-up, and changes in proportionate reinforcement related to substance-free activities mediated the relation between the intervention and reductions in alcohol use. Further, having substance-free next-day responsibilities (e.g., employment, classes, volunteer work) have been linked to lower alcohol demand, as measured by a behavioral economic task, the alcohol purchase task (Murphy & MacKillop, 2006), that quantifies hypothetical alcohol consumption and alcohol-related expenditures as a function of drink prices (Joyner et al, 2019). A review of clinical research on associations between social support and smoking (Fisher, 1996) supported conceptualizing both activities as commodities that could substitute for one another; specifically, social support is effective in reducing smoking, while it is available but this salutary substitution relationship diminishes when access is constrained.…”
Section: Present Status Of Research On Addictive Behavior As Behavior...mentioning
confidence: 99%
“…Thus, these concurrent choice studies contradict the prediction of compulsion theory that dependence is driven by a maladaptive S-R association that renders drug-seeking invulnerable to immediate punishment [ 17 ] (for a more extensive critique of compulsion theory see [ 22 , 51 ]). It is interesting to note that other studies that tested the impact of imagined next day responsibilities on measures of drug demand (willingness to pay for the drug), found evidence that dependence may be linked to insensitivity to these future costs [ [52] , [53] , [54] , [55] ]. Thus, dependence may be linked to an inability to incorporate future costs into decision making consistent with delay discounting models of addiction [ 21 ], but there is little evidence that dependence is linked to insensitivity to immediate costs, an observation that is inconsistent with compulsion theory [ 17 ].…”
Section: Relative Value Of Drugs Versus Alternative Rewards Underpinsmentioning
confidence: 99%
“…In other words, an individual who drank four drinks last week may have drunk more if drinks were more available or if they had seen their friends. Although standard APTs define constraints as increasing price, a substantial literature has demonstrated that alcohol demand changes under a variety of other constraints [3], such as when one has to drive after drinking [4], when there is a next‐day responsibility (opportunity cost [5]) and when friends are no longer present [6].…”
mentioning
confidence: 99%